The national strategies in the reorientation of students' inclination towards science and technology / Ahmad Mohd. Isa - Mohd. Isa, Ahmad (1992)
I would like to begin by looking at a brief history of our educational policy since we gained independence from Britain in 1957 with particular reference to the National Strategies in the Reorientation of Students' Inclination towards Science and Technology. We inherited the British Colonial Educational policy and made changes to prepare ourselves for independence. At the beginning of independence the Razak Report became the basis of our present day educational policy and practices. During the British Administration students obtained secondary education through the medium of English. At that time students studied General Science up to school certificate level. In some selected schools Additional General Science was offered as an extra qualification to enable students to go for further studies in science related fields such as medicine, engineering and architecture. Only a handful of students managed to grab the opportunities. Most of them find some difficulties during their studies at higher levels. At the early stage of independence we experienced shortage of science and mathematics teachers. Most of our trained teachers were hardly qualified to teach Additional General Science because their knowledge of science was only confined to General Science. Most of the science teachers came from overseas as contract officers. They were put to teach Additional General Science and most of them returned to their own countries after completing their contracts.